Caring as sharing. Negotiating the moral boundaries of receiving care. Issue 5 (19th October 2020) - Sand Andersen, Rikke; McArtney, John; Rasmussen, Birgit H.; Bernhardson, Britt-Marie; Hajdarevic, Senada; Malmström, Marlene; Ziebland, Sue
ABSTRACT: Informal caregiving is increasingly considered a health care delivery-resource within the North European welfare states. While 'informal' often refers to non-professional, 'caregiving' connotes both affective concern (caring about) and practical action (caring for). This duality of meanings, however, often refers to the one direction in which care is given. Care, we suggest, is relational and also requires that people receiving care are able to or wanting to share their needs. Informal caregiving thus requires sharing. Based on 155 semi-structured, narrative interviews with people with lung or bowel cancer, living in Denmark, Sweden or England, this paper explores how and with whom people 'share' when they fall ill. We approach sharing as a heuristic for reflecting on informal-caregiving, and illustrate how being cared for or asking for care are entangled with the management of social risks and notions of selfhood. We conclude that informal caregiving should explicitly be recognised as morally and sympathetically committed practices, which attend to the diversity of local moral worlds of patients, their needs and experiences.